THE INFLUENCE OF BUDGET PARTICIPATION ON MANAGERIAL PERFORMANCE - Mardani Supranata; Jasman (ITB AAS INDONESIA, 2025)
The purpose of this study was to examine the effect of budget participation on managerial performance in manufacturing companies in Indonesia. The data used in this study were obtained from distributing questionnaires to midle-up managers of manufacturing companies in Indonesia. The questionnaires processed were 200 questionnaires. The study conducted during 2024. The analysis method used is simple linear regression test. The results show that budget participation on managerial performance has a significant and positive effect on managerial performance. This research suggests that shareholders ask managers to implement a budget participation policy which requires all levels of managers to be involved in budget preparation in order to improve managerial performance.Â